Evaluación de mezclas de polihidroxibutirato (P3HB) con aditivos para la obtención de un material polimérico (2019)
This project aims to evaluate those additives that have compatibility and favor the physicochemical properties of P3HB, so that the additives were selected polylactic acid (PLA), polyethylene glycol 400 (PEG 400) and nanocrystalline cellulose (CNC), with those that were binary and ternary mixtures at different concentrations and temperatures; The mixtures were made from the solvent casting technique where chloroform was used to dilute both the P3HB and the additives. Once the blenders were made, they were characterized by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) tests; those that showed favorable results resistance were determined from a mechanical stress test. As for the composite material that was obtained, it was shown that the CNC did not show great affinity, while the PLA showed high compatibility with the P3HB. Similarly, the plasticizer (PEG) caused an improvement in the thermal properties, although despite this, when analyzing the effect on the mechanical properties for the P3HB / PLA / PEG fills there was an unfavorable effect compared to those mixtures of P3HB / PLA without PEG. It was concluded by characterizing the material that the one that showed a high melting point and less deformation was the mixture of P3HB / PLA at concentrations 70/30 respectively. According to these results, the production of the material was considered and a study of costs of raw material, equipment, energy and water consumption was carried out.